PENERAPAN PENGGUNAAN MEDIA EDUCAPLAY BERBASIS FROGGY JUMPS TERHADAP HASIL BELAJAR IPAS MURID DI KELAS IV SDN 72 PALEMBANG - Supari, Padilah; Neta Dian Lestari; Sonia Anisah Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the less than optimal student grades, especially in fourth grade students of SD Negeri 72 Palembang which is marked by 20 students not achieving (KKM) and 13 students achieving (KKM) for science learning. This study aims to determine the effect of the application of Froggy Jumps-based Educaplay media on the science learning outcomes of fourth grade students of SDN 72 Palembang. This study uses a quasi-experimental method with a nonequivalent control group design. The population in this study were all fourth grade students of SD Negeri 72 Palembang. The research sample consisted of classes IV C and IV D which were determined using a purposive sampling technique. Data collection techniques were carried out through tests and documentation. The average value of the experimental class was 83.28, the average value of the control class was 69.22. Hypothesis testing in this study used an independent sample t-test. The results of the hypothesis test show that the t-value is 4.285 > t-table 1.999 and the significance value (Sig. 2-tailed) is 0.000 < 0.05, so that H₀ is rejected and Hₐ is accepted. Thus, it can be concluded that the Educaplay media based on Froggy Jumps has an impact on the learning outcomes of fourth-grade students of SDN 72 Palembang.